PEMBERDAYAAN MASYARAKAT SEKITAR MASJID MELALUI PENDAMPINGAN LITERASI DIGITAL SEBAGAI PENANGKAL RADIKALISME - Maftukhin; Amrullah Ali Moebin; Naibin; Muchamad Rudi Cahyono (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Information overload is more extensive in this digital era, allowing any information to bombard anyone, anytime, and anywhere. Social media algorithms can no longer contain the content that will be consumed by the public. However, they can curate content based on user preferences. Users have limited control over preventing this, including being warned about the presence of radical content. Despite that, the spread of radical content is not only done massively through the internet but can also occur in Islamic study forums. Forums that contain radical movements are widespread within Islam, happening anywhere. Therefore, it is important for society to be aware of the radicalism that threatens the values of Islamic teachings and the principles of Ahlul Sunnah wal Jamaah. One way to counteract radicalism is by sharpening critical thinking and enriching knowledge and literacy. The dissemination of knowledge can be carried out in various forums, including within mosques. Mosques themselves have many functions beyond being places of worship. Understanding these functions and maximizing them is key to addressing the spread of radicalism